The Relationship Between Self-Efficacy And Library Anxiety Among College Students In Bekasi City - Sharfina Tamimi; Sarita Candra Merida; Tugimin Supriyadi (Socrates: Journal of Education, Philosophy and Psychology, 2026)
Libraries are an important learning resource that supports students’ academic progress; however, their use is not always optimal because some students still experience library anxiety a feeling of anxiety, fear, or discomfort when using library facilities and services. One psychological factor believed to be related to this condition is self-efficacy, which is an individual’s belief in their ability to tackle and complete tasks. This study aims to determine the relationship between self-efficacy and library anxiety among students in Bekasi City. This study employs a quantitative method with a correlational approach. The study sample consisted of 120 active students in Bekasi City, selected through a non-probability sampling technique using incidental sampling. Data were collected using a self-efficacy scale and a library anxiety scale, then analyzed using Spearman’s correlation test with IBM SPSS Statistics 25. The results indicate that there is no significant relationship between self-efficacy and library anxiety among college students in Bekasi City. This finding suggests that library anxiety is not directly related to general self-efficacy; therefore, there may be other factors more specific to the context of library use that influence the emergence of this anxiety.